Gold(III) Corroles for High Performance Organic Solar Cells. (22nd April 2014) - Lai, Shiu‐Lun; Wang, Lin; Yang, Chen; Chan, Mei‐Yee; Guan, Xiangguo; Kwok, Chi‐Chung; Che, Chi‐Ming
<x xml:space="preserve">Abstract</x> While the use of molecular materials having long‐lived triplet excited state(s) for harvesting solar energy could be an effective approach to boost up the power conversion efficiency (PCE) of organic solar cells (OSCs), the performances of this kind of OSCs as reported in the literature are low (< 2.9% PCE attained for the vacuum‐deposited OSCs). Herein is described the realization of high performance OSCs by using gold(III) 5, 10, 15‐triphenylcorrole (Au‐C1), gold(III) 10‐(p‐trifluoromethylphenyl)‐5, 15‐diphenylcorrole (Au‐C2), and gold(III) 10‐(pentafluorophenyl)‐5, 15‐diphenyl‐corrole (Au‐C3), as electron‐donors. These gold(III) corroles display excited state lifetimes of ≥ 25 μs and low emission quantum yields of < 0.15%. With the complexes Au‐C1, Au‐C2, and Au‐C3, vacuum‐deposited OSCs, which give PCEs of 2.7%, 3.0%, and 1.8%, respectively, are fabricated. The PCE can be further boosted up to 4.0% after thermal treatment of the OSC devices. Meanwhile, a solution‐processed OSC based on Au‐C2 with a high PCE of 6.0% is fabricated. These PCE values are among the best reported for both types of vacuum‐deposited and solution‐processed OSCs fabricated with metal‐organic complexes having long‐lived excited states as electron‐donor material. The underlying mechanism for the inferior performance of the reported OSCs is discussed.